2022
DOI: 10.3389/fmed.2022.912367
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of COVID-19 Patients Infected by the Omicron Variant of SARS-CoV-2

Abstract: BackgroundCurrently, as the omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surges amid the coronavirus disease 2019 (COVID-19) pandemic, its clinical characteristics with intrinsic severity and the protection from vaccination have been understudied.MethodsWe reported 169 COVID-19 patients that were infected with the omicron variant of SARS-CoV-2 and hospitalized in Suzhou, China, from February to March 2022, with their demographic information, medical/immunization history, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 52 publications
10
61
0
1
Order By: Relevance
“…Omicron replicated faster than all other SARS-CoV-2 variants in the bronchi but less efficiently in the lung parenchyma ( 14 ). This is compatible with the epidemiological observations that infection with Omicron produces higher infectivity but a less severe disease ( 7 , 15 , 16 ). No studies to date have reported any specific symptoms of infection caused by the Omicron BA.2 variant.…”
Section: Discussionsupporting
confidence: 91%
“…Omicron replicated faster than all other SARS-CoV-2 variants in the bronchi but less efficiently in the lung parenchyma ( 14 ). This is compatible with the epidemiological observations that infection with Omicron produces higher infectivity but a less severe disease ( 7 , 15 , 16 ). No studies to date have reported any specific symptoms of infection caused by the Omicron BA.2 variant.…”
Section: Discussionsupporting
confidence: 91%
“…As of June 2022, the B.1.1.529 (Omicron) variant remains prevalent (Karim and Karim 2021;Petersen et al 2022). Although this variant is considered to result in milder symptoms with better outcomes compared to prior variants, disease is still not mild (Nealon and Cowling 2022;Zhang et al 2022). In addition to the change in severity of Omicron, the variant has also been suggested to show a lower prevalence of smell and taste disturbances, and a higher prevalence of sore throat and odynophagia (Piersiala et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of asymptomatic infection in our cohort was lower than studies described previously from South Africa (23%) and China (46.7%) but was similar to a cohort of healthcare personnel from New York (11%) during Omicron epidemic. [19,20,21] The actual proportion of asymptomatic infection in our cohort could be overestimated as the clinical data could have been submitted during pre-symptomatic stage of infection. Although being symptomatic and having exposure history were the most common reasons for undergoing testing, regular mandatory RAT played an important role in promote testing as up to 26.66% of the infected staff were identified as a result of such policy.…”
Section: Discussionmentioning
confidence: 97%